Improving the carbon efficiency in the bio-production of citramalic acid in Escherichia coli - Lebeau, Juliana Laurence Dominique (2018)
Methacrylic acid (MAA) is a bulk chemical used in the synthesis of acrylic polymers as well as for the manufacture of many different products such as resins, and paints. However, the industrial manufacturing processes for MAA production involve toxic raw materials that are reliant on availability and economic variability of petroleum derived compounds. Global consumption and market of acrylics keep growing, rendering constant production processes as well as price stability highly desirable.